Role and place of telecommunication systems in teaching neurosurgery - Tsymbaliuk, V. I.; Semisalov, S. Ya.; Kardash, A. M. (Ukrainian Neurosurgical Journal)
The circuit of training of the students on a speciality «Neurosurgery» with the help of telecommunication technologies is developed. The offered system provides more active participation of the students in mastering learning of a material, using for expansion of the knowledge as information base available on a site of the teacher of high SCHOOL, and sites of other HIGH SCHOOLS and countries. The offered system does not require(demand) significant material inputs, assumes use of computer engineering of enough low level (Pentium I—II) and is intended not only to impart knowledge on neurosurgery, but also to bring up at the students ability to independent work with use of the newest information technologies.